فعالية الذات وعلاقتها بقلق المستقبل لدى الطلبة المقبلين على التخرج - منتصر, مسعودة (جامعة الوادي University of Eloued, 2017)
ملخص الدراسة: هدفت الدراسة إلى معرفة علاقة فعالية الذات بقلق المستقبل لدى الطلبة المقبلين على التخرج دراسة ميدانية على طلبة السنة الثالثة جامعي والثانية ماستر علوم اجتماعية بجامعة الوادي.، وتم إجراء الدراسة على عينة تكونت من (91) طالبا وطالبة من قسم علوم التربية بكلية العلوم الاجتماعية جامعة الشهيد حمه لخضر بالوادي ،وقسمت إلى (43) طالباً من طلبة السنة الثالثة جامعي ، و (48) طالباً من طلبة السنة الثانية ماستر، وبإتباع المنهج الوصفي بأسلوبيه ألارتباطي و السببي المقارن . ولاختبار فرضيات الدراسة تم استخدام معامل ارتباط بيرسون ، و اختبار (ت) لدلالة الفروق بين المتوسطات لعينتين وتم التوصل إلى النتائج الآتية :- لا توجد علاقة ارتباطيه دالة إحصائيا بين فعالية الذات وقلق المستقبل لدى الطلبة المقبلين على التخرج . - لا توجد فروق ذات دلالة إحصائية في فعالية الذات بين طلبة السنة الثالثة جامعي وطلبة السنة الثانية ماستر بكلية العلوم الاجتماعية جامعة حمه لخضر بالوادي . - لا توجد فروق ذات دلالة إحصائية في قلق المستقبل بين طلبة السنة الثالثة جامعي وطلبة السنة الثانية ماستر بكلية العلوم الاجتماعية جامعة حمه لخضر بالوادي . This study was aimed to detect the relationship of self-efficacy with and future anxiety in graduating students. A field study on third year university students and the second year master's students of social sciences at El Oued University. The study was conducted on a sample composed of (91 male and female), students in the department of social sciences, faculty of Humanities and Social Sciences, university of Eshahid Hamma Lakhdar El Oued, and it was divided into (43) students of third-year students, and (48) students of second-year master students, and following The descriptive approach with its correlative and causative methods. To test the hypotheses of the study, we used Pearson's correlation coefficient and T-test to indicate the differences between the means of two samples. The study concluded the following results: There was no statistically significant correlation between self- efficacy and future anxiety among graduating students; -There were no statistically significant differences in self- efficacy between third year students and second year master's students at the faculty of Social Sciences, university of eshahid Hamma Lakhdar El oued; here were no statistically significant differences in future anxiety between third year students and second year master's students at the faculty of Social Sciences, university of eshahid Hamma Lakhdar El oued.
دراسة ميدانية على طلبة السنة الثالثة جامعي والثانية ماستر علوم اجتماعية بجامعة الوادي.
مقال
Keywords: فعالية الذات، الذات، القلق، قلق المستقبل ،طلبة السنة الثالثة جامعي, طلبة الثانية ماستر; Self-efficacy; self; anxiety; the future anxiety; university students